Adsorptive stripping voltammetry of hen-egg-white-lysozyme via adsorption-desorption at an array of liquid-liquid microinterfaces - Alvarez de Eulate, E.; Arrigan, Damien (American Chemical Society, 2012)
Electrochemical adsorption and voltammetry of hen-egg-white-lysozyme (HEWL) was studied at an array of microinterfaces between two immiscible electrolyte solutions (µITIES). Adsorption of the protein was achieved at an optimal applied potential of 0.95 V, after which it was desorbed by a voltammetric scan to lower potentials. The voltammetric peak recorded during the desorption scan was dependent on the adsorption time and on the aqueous phase concentration of HEWL. The slow approach to saturation or equilibrium indicated that protein reorganization at the interface was the rate-determining step and not diffusion to the interface. For higher concentrations and longer adsorption times, a HEWL multilayer surface coverage of 550 pmol cm-2 was formed, on the basis of the assumption that a single monolayer corresponded to a surface coverage of 13 pmol cm-2. Implementation of adsorption followed by voltammetric detection as an adsorptive stripping voltammetric approach to HEWL detection demonstrated a linear dynamic range of 0.05-1 µM and a limit of detection of 0.03 µM, for 5 min preconcentration in unstirred solution; this is a more than 10-fold improvement over previous HEWL detection methods at the ITIES. These results provide the basis for a new analytical approach for label-free protein detection based on adsorptive stripping voltammetry.